Angiogenesis: 2D Nanosilicates Loaded with Proangiogenic Factors Stimulate Endothelial Sprouting (Adv. Biosys. 7/2018). Issue 7 (13th July 2018) - Howell, David W.; Peak, Charles W.; Bayless, Kayla J.; Gaharwar, Akhilesh K.
Abstract : 2D nanosilicates as a platform technology to sequester and deliver a multitude of therapeutic growth factors to stimulate and direct cellular functions are presented by Akhilesh K. Gaharwar and co‐workers in article number1800092 . The high surface area and charged characteristics of 2D nanosilicates prolong the release of therapeutic biomolecules while maintaining their bioavailability.